Jatrophainolides A–C, new cembrane-type diterpenoids with PTP1B inhibitory activity from the root bark of Jatropha integerrima. (April 2020) - Zhang, Dong-Bo; Wang, Zheng; Liang, Yan-Ni; Yu, Jin-Gao; Zhang, Zhen; Liu, Shi-Jun; Zhang, Zhao; Song, Zhong-Xing; Tang, Zhi-Shu; Duan, Dong-Zhu
Graphical abstract: Highlights: Three new cembrane diterpenoids were isolated from Jatropha integerrima . The new structures were established by extensive spectroscopic analyses. All isolates displayed potential inhibitory activities against PTP1B. Abstract: Three new 14-membered cembrane-type diterpenoids, jatrophainolides A–C (1 −3 ), were isolated from the root bark of Jatropha integerrima Jacq. Thier structures were established on the basis of extensive spectroscopic techniques including NMR spectroscopy and mass spectrometry. Of these isolates, compounds 1 and 2 were a pair of isomers with the E/Z configurations of Δ 1, 2 double bond. All compounds displayed potential inhibition against human protein tyrosine phosphatase 1B (PTP1B) with IC50 values of 6.38, 25.9, and 27.4 μ M, respectively.